GOVERNANCE OF LOCAL GOVERNMENT OF WEST KALIMANTAN AGAINST ILLEGAL LOGGING - Siba, M. Angela Merici (Journal of Islamic World and Politics, 2021)
Illegal logging is unauthorized logging and timber theft performed by the perpetrators wanting to manage forests for their individual needs. It has a negative impact on the habitat of forests and communities in West Kalimantan. The felled trees are used for the needs of the perpetrators and exported to timber buyer countries. High timber demands have triggered the actors to perform such a crime. It occurs because some actors carry out document forgery in managing forests. This research utilized the political system theory from David Easton and discovered that the local government of West Kalimantan has made illegal logging rules. However, illegal logging remains to exist because the governance from the local government has not been maximized in issuing not binding policies and lack socialization from the government to the community regarding illegal logging.